Career Considerations in Nurse-Led Traditional Chinese Medicine Clinics: a Two-Center Qualitative Study - Zhao FY; Kennedy GA; Gilbert J; Conduit R; Xu P; Yue LP; Zhang WJ; Wang YM; Ho YS; Fu QQ; Zheng Z (Risk Management and Healthcare Policy, 2024)
Fei-Yi Zhao,1,2,* Gerard A Kennedy,3– 5,* Julia Gilbert,3,* Russell Conduit,4,* Peijie Xu,6 Li-Ping Yue,1 Wen-Jing Zhang,2 Yan-Mei Wang,2 Yuen-Shan Ho,7 Qiang-Qiang Fu,8 Zhen Zheng4 1Department of Nursing, School of International Medical Technology, Shanghai Sanda University, Shanghai, 201209, People’s Republic of China; 2Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200071, People’s Republic of China; 3Institute of Health and Wellbeing, Federation University, Mount Helen, VIC, 3353, Australia; 4School of Health and Biomedical Sciences, RMIT University, Bundoora, VIC, 3083, Australia; 5Institute for Breathing and Sleep, Austin Health, Heidelberg, VIC, 3084, Australia; 6School of Computing Technologies, RMIT University, Melbourne, VIC, 3000, Australia; 7School of Nursing, Faculty of Health and Social Sciences, The Hong Kong Polytechnic University, Hong Kong SAR, People’s Republic of China; 8Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuen-Shan Ho, School of Nursing, Faculty of Health and Social Sciences, The Hong Kong Polytechnic University, Hong Kong SAR, People’s Republic of China, Tel +852 2766-6410, Fax +852 2364-9663, Email janice.ys.ho@polyu.edu.hk Qiang-Qiang Fu, Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of China, Tel + 86 021-6569 0520, Fax + 86 021-6569 6249, Email qiangqiang.fu@tongji.edu.cnBackground: Growing demand exists for high-quality Traditional Chinese Medicine (TCM) care, particularly through Nurse-led TCM clinics (TCM-NLCs). Nurses with extensive experience in TCM departments represent a potential workforce for this healthcare model. This qualitative study aims to investigate the willingness of these candidates to engage in TCM-NLCs, with a specific focus on their main concerns and apprehensions when facing new challenges.Methods: Individual semi-structured face to face interviews were conducted with senior nurses from two TCM hospitals in Shanghai. Each participant had a minimum of three years of work experience in a TCM related department. Conventional qualitative content analysis was utilized.Results: Fourteen participants were interviewed and data saturation was achieved. Nurses exhibited strong interest in practicing in TCM-NLCs. They believed that such innovative TCM nursing service model not only extends nursing role, provides greater empowerment and opportunities for professional development but also meets patients’ diverse healthcare needs, reduces reliance on other healthcare providers such as doctors, and increases hospital revenue. However, challenges such as deficiencies in evidence-based TCM nursing education, the absence of standardized practice guidelines, and limited prescriptive privileges were identified as primary obstacles to engaging in TCM-NLCs practice, potentially undermining the specialization of this advanced nursing practice model.Conclusion: Although the nurses interviewed were highly motivated, they generally lacked confidence to practice independently in TCM-NLCs. A pressing priority is to address their concerns by providing appropriate resources as well as education and policy support to enhance their competency and ensure their practice autonomy, therefore building a more qualified pool of professionals for advanced TCM nursing practice.Keywords: nurse-led clinic, nurse career development, traditional Chinese medicine nursing, qualitative study, advanced nursing practice, specialist nurses